Fire risk perpetuates poverty and fire use among Amazonian smallholders. (July 2020) - Cammelli, Federico; Garrett, Rachael D.; Barlow, Jos; Parry, Luke
Highlights: Forest fires, forest degradation and poverty coexist in the Brazilian Amazon Many smallholder farmers are locked-into low income and increasingly risky agricultural fire use We show that exposure to fire risk increases smallholders' dependence on fire intensive land uses Mitigating fire risk requires coordinated investments in fire control or fire free land uses Policies favoring fire risk mitigation reduce degradation, CO2 emissions, and poverty Abstract: Forest fires exacerbate carbon emissions, threaten biodiversity and cause welfare losses to local populations. Most fires accidentally ignite from mismanaged swidden and pasture fires. We provide evidence that fire risk in the Brazilian Amazon, the world's largest remaining tropical forest, perpetuates low yield and environmentally degrading agricultural activities. Using a combination of household interviews and remotely sensed data on fire occurrence in Eastern Amazon municipalities of Paragominas and Santarém, we show that smallholders in consolidated farm-forest frontier regions are locked into a vicious cycle that inhibits their adoption of fire-free practices. Households that invest in more capital-intensive fire-free agricultural technologies experience greater revenue losses from escaped fires than non-fire users. Changes in revenues are as sensitive to these fire impacts as they are to changes in physical capital investments. To overcome this fire-poverty trap, a "big push" of coordinated local incentives is needed. Policies mitigating fire risk may achieve a triple-win that reduces greenhouse gas emissions, forest degradation, and fosters inclusive economic development.